2015
DOI: 10.1002/ejlt.201500363
|View full text |Cite
|
Sign up to set email alerts
|

Substrate selectivity of Novozym 435 in the esterification of glycerol with an equimolar mixture of linoleic, conjugated linoleic, and pinolenic acids

Abstract: The selectivity of Novozym 435, an immobilized Candida antarctica lipase B toward linoleic (LA), conjugated linoleic (CLA), and pinolenic acids (PLA) was investigated in the esterification of glycerol with an equimolar (27.3 mol% each) mixture of the fatty acids (FAs) in a solvent‐free system to prepare triacylglycerols (TAGs) with anti‐obesity effects. The maximal TAG content of 98.9 wt% was achieved under the following conditions: temperature, 70°C; reaction time, 24 h; glycerol‐to‐FA mixture molar ratio, 1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…For the lipase Novozyme 435, the increase of DHA content might be related to its random behavior and, also, to the 2‐selectivity toward fatty acids with higher degree of unsaturation. Effectively, Woo et al described that Novozyme 435 showed a tendency to esterify the most unsaturated fatty acids at the sn ‐2 when the susbtrate was composed of fatty acids with the same number of carbons but different unsaturation degree. Regarding to TL IM, it might be feasible that, in such a low water content and being 1,3‐DAG the main substrate, the esterification in the central position also takes place.…”
Section: Resultsmentioning
confidence: 99%
“…For the lipase Novozyme 435, the increase of DHA content might be related to its random behavior and, also, to the 2‐selectivity toward fatty acids with higher degree of unsaturation. Effectively, Woo et al described that Novozyme 435 showed a tendency to esterify the most unsaturated fatty acids at the sn ‐2 when the susbtrate was composed of fatty acids with the same number of carbons but different unsaturation degree. Regarding to TL IM, it might be feasible that, in such a low water content and being 1,3‐DAG the main substrate, the esterification in the central position also takes place.…”
Section: Resultsmentioning
confidence: 99%
“…An FFA fraction containing ≈13 wt% PLA was prepared by saponification of the NPNO according to the method described in our previous study . NPNO (100 g) was saponified with 400 mL of 10 wt% NaOH in 75 vol% ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…An FFA fraction containing ≈44 wt% PLA was prepared via urea crystallization of the FFA containing ≈13 wt% PLA obtained above, following the method described in our previous study . The FFA fraction (50 g) containing ≈13 wt% PLA and urea (150 g) were both dissolved in methanol (500 mL), and the resulting mixture was refluxed at 250 °C until the urea was dissolved completely.…”
Section: Methodsmentioning
confidence: 99%
“…From the experimental results in sections 3.2 and 3.3, we concluded that the optimal conditions for the preparation of PLA concentrates from the FFA fraction obtained from pine nut oil are a temperature of 85 , an n-hexane-to-FFA ratio of 30:1, and a fractionation time of 36 h. Under these conditions, PLA concentrates containing 69.8 wt PLA were obtained with a yield of 77.4 wt based on the initial weight of PLA in the FFA fraction. Woo et al 5 used urea crystallization to prepare PLA concentrates containing 47 wt PLA with a yield of PLA of 77 wt from the FFA fraction obtained from Korean pine nut oil with a PLA content of 13 wt . Lee et al 6 and Zhao et al 7 found that ethyl ester forms of PLA concentrates can be prepared by C. antarctica lipase B-catalyzed ethanolysis of pine nut oil.…”
Section: Optimal Fractionation Conditionsmentioning
confidence: 99%
“…Finally, as shown in Table 1, with the exception of 20:0, 11 different species of FA contained in the original FFA fraction remained in the PLA concentrates. Woo et al 5 reported that PLA concentrates prepared by urea crystallization from Korean pine nut oil containing 13 different species of FA only contained 7 species of FA, despite the relatively low PLA content of 47 wt . In particular, all SFA i.e., 16:0, 18:0, and 20:0 were eliminat-ed from the PLA concentrates.…”
Section: Optimal Fractionation Conditionsmentioning
confidence: 99%